GENESIS AND FORMATION OF DESIGN LANGUAGE OF VISUAL IMAGES AND COMMUNICATIVE PRACTICES IN THE CONTEXT OF THE CULTURAL AND ARTISTIC HERITAGE OF UKRAINE - Яковлев, М. І.; Кара-Васильєва, Т. В.; Чуйков, О. Д.; Шмагало, Р. Т.; Чепелюк, О. В. (Art and Design, 2023)
Purpose. The purpose of the work is to study the historical development of artistic and graphic language and visual perception of images during the transmission of information from ancestors to descendants, which in modern society becomes the basis for the formation of the harmonious integrity of Ukrainian visual culture. Methodology. The work is based on the use of historical and cultural, comparative, and hermeneutic methods. In addition, the methodology of the system approach was used, which allows us to consider visual communications as an integrated field of human-environment interaction in the context of the achievements of Ukrainian art. Results. The study presents the dynamics of development and systematizes the historical-cultural art-theological view of visualizing the references of the ancient world to modern society. The analysis of the artistic monuments of the Ukrainian cultural heritage made it possible to determine the general orientation of the artistic and project language of visual images and to highlight the peculiar ethno-national, aesthetic and ecological aspects that contribute to the sustainable development of society. It has been proven that the development of visual language and design practices took place in the directions of improving the means of artistic expression, deepening subject interactions, strengthening communicative processes of a spectacular and cult nature, involving natural phenomena in communication, as well as organizing mass complex actions aimed at the revival of Ukrainian culture. The results of the research are important for solving the problems of global information overload of the environment and visual perception by rethinking the traditional cultural-artistic and natural aspects in modern visual culture. Scientific novelty. The research for the first time substantiated and identified the interrelationships of the features of information exchange with the help of artistic images and artistic crafts from ancient times to the present in the visual subject environment. In the work, for the first time, an attempt is made to give a general description of the processes of development and formation of the visual graphic language of communicative processes, the basis of which is the interpretation of cultural and artistic heritage. It is proved that the course of ethno-cultural processes, which took place on the territory of Ukraine from ancient times to the present, is important for understanding the origins of communicative design. Practical significance. An analysis of the historical perspective of the dynamics of the development of folk art is presented on the example of folk traditions of Ukrainian art, and the directions of their introduction into modern visual culture are outlined. The results can become the basis for further theoretical studies of visual communications and can be used by practitioners during the design and stylization of the arrangement of modern space, as well as a basis for the formation of the systemic thinking of designers in scientific research and the educational process.